2015
DOI: 10.1088/1748-6041/10/1/015026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epidermal growth factor-loaded mucoadhesive films on wounded oral tissue rafts

Abstract: Current treatments for traumatic oral mucosal wounds include the gold standard of autologous tissue and alternative tissue engineered grafts. While use of autografts has disadvantages of minimal availability of oral keratinized tissue, second surgery, and donor site discomfort, tissue engineered grafts are limited by their unavailability as off-the-shelf products owing to their fabrication time of 4–8 weeks. Hence, the current work aimed to develop a potentially cost-effective, readily available device capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, the EGF treatment caused a hyperparakeratotic response and induced other structural abnormalities including thickening of the spinous layer, intra-and intercellular edema, and pyknotic nuclei. In addition, no improvements in wound closure were observed (Ramineni et al 2015).…”
Section: Oral Pathologymentioning
confidence: 94%
See 1 more Smart Citation
“…However, the EGF treatment caused a hyperparakeratotic response and induced other structural abnormalities including thickening of the spinous layer, intra-and intercellular edema, and pyknotic nuclei. In addition, no improvements in wound closure were observed (Ramineni et al 2015).…”
Section: Oral Pathologymentioning
confidence: 94%
“…In addition, the EpiGingival model was used to study the effects of biofilms as they relate to the expression of junctional proteins within the tissue and possible implications of periodontal disease (Belibasakis et al 2015). Ramineni et al 2015 investigated whether mucoadhesive films impregnated with epithelial growth factor (EGF) could be used to treat traumatic oral mucosal wounds. The mucoadhesive films delivered bioactive EGF in a sustained manner to punch biopsy wounds inflicted to the full thickness EpiOral tissue.…”
Section: Oral Pathologymentioning
confidence: 99%
“…27,30,31 In particular, the report by Ramineni and coworkers successfully demonstrated that a concentration regime between 1-5 ng mL −1 EGF provided maximal cell migration, cellular differentiation and wound healing. 32 Similar EGF levels were attained after 72 hours in our case; hence, this time point was chosen for the following in vitro investigations.…”
Section: Biomaterials Science Papermentioning
confidence: 67%
“…The available data suggest the promise of EGF purposed at improving oral wound healing. To recapitulate, stimulation of proliferation and migration of oral keratinocytes, stimulation of gingival fibroblasts mitogenesis and increase of collagen synthesis (Kim et al., ; Pansani et al., ; Ramineni, Fowler, Fisher, Cunningham, & Puleo, ) are among the cellular events through which exogenous EGF is harnessed to facilitate the wound repair in vitro. Nevertheless, whether EGF‐based treatment is able to facilitate the repair of acute injuries healing by secondary intention remains unknown.…”
Section: Introductionmentioning
confidence: 99%